2022
DOI: 10.7717/peerj.13644
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and functional nematode diversity in Maldivian coral degradation zones: patterns across reef typologies and depths

Abstract: The intensification of dredging and infilling activities in lagoons and on coral reefs are common practices in the Maldivian archipelago, and these activities alter the biodiversity of the bioconstructors and the functioning of the ecosystem. The alteration of environmental factors can also affect inconspicuous fauna, such as free-living nematodes. The implications of a reduction in biodiversity may transcend decreased taxonomic diversity, resulting in changes in functional diversity and redundancy; however, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Similar findings have been reported in other coral reef ecosystems. For instance, a study on the morphological identification of 2010 nematodes from the Maldives coral reefs revealed that all 173 identified genera belonged to Enoplea and Chromadorea [18]. In comparison, this study identified more than 30 families across the two coral reef regions, with seven families being common to both regions.…”
Section: Nematode Biodiversity In the South China Sea Coral Reefsmentioning
confidence: 72%
“…Similar findings have been reported in other coral reef ecosystems. For instance, a study on the morphological identification of 2010 nematodes from the Maldives coral reefs revealed that all 173 identified genera belonged to Enoplea and Chromadorea [18]. In comparison, this study identified more than 30 families across the two coral reef regions, with seven families being common to both regions.…”
Section: Nematode Biodiversity In the South China Sea Coral Reefsmentioning
confidence: 72%